Sidang Pemeriksaan Setempat Pada Peradilan Hubungan Industrial Dalam Pelaksanaan Asas Peradilan Cepat Tepat Adil Dan Murah - Alim Jair; Azad Gamil (Hakim, 2023)
Good service, as well as interesting innovations, of course will increase public interest in paying their obligations, namely paying taxes. At least, good service will not make people lazy to come to the office to pay taxes. Good organizational performance, of course, is needed in this case. And in achieving good organizational performance, good cooperation is needed from many parties. In particular, individuals who work as service providers at the Pekanbaru City Regional Revenue Agency.